From Reflection to Revision: Exploring Self-Regulated Learning in EFL Writing Portfolios - Ana Zulianingrum (Journal of English Language and Education, 2026)
This study addresses the limited attention given to learners’ internal self-regulatory processes in portfolio-based EFL writing instruction, particularly in non-Western tertiary contexts such as Indonesia. While previous research on self-regulated learning (SRL) in EFL writing has often emphasized measurable writing outcomes, including grammatical accuracy, coherence, and text organization, less is known about how portfolios support learners’ goal setting, self-monitoring, and reflection during the writing process. Employing a qualitative case study approach supported by descriptive writing-performance data, this study investigated 30 Indonesian undergraduate EFL learners enrolled in a writing course. Data were collected through writing portfolios, semi-structured interviews, classroom observations, and reflective journals over a four-week instructional period. Thematic analysis revealed that portfolio-based writing tasks fostered SRL behaviors by encouraging iterative drafting, strategic revision, and critical self-assessment. However, students also encountered challenges related to time management, limited reflective depth, and difficulty self-assessing higher-order writing skills. These findings highlight the need for explicit instructional scaffolding, structured reflection prompts, and sustained teacher and peer feedback. Overall, the study suggests that portfolio-based writing instruction can enhance learner autonomy and writing proficiency by creating a structured, reflective, and process-oriented learning environment.